2021
DOI: 10.1007/s10953-021-01068-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Solubility of Hydrochloride Mucolytic Agents

Abstract: Two widely used active pharmaceutical ingredients (API), ambroxol hydrochloride (AMB·HCl) and bromhexine hydrochloride (BMH·HCl), belong to the expectorant and mucokinetic group of drugs. Their applications are found in the treatment of the upper respiratory tract and bronchopulmonary diseases. The compounds have similar chemical structures, but are different enough to distinguish their physicochemical properties. To understand better the bioavailability of the drugs a series of experiments was performed to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In addition, it should be noted that lactose monohydrate, one of the excipients in FT formulation, also interacts with moisture-sensitive drugs and affect the stability of the drug [27,44]. Koivisto et al [45] reported that Mg stearate (excipient as well) properties strongly depend on the moisture content and its hydration state [21]. Literature data confirm that magnesium stearate might absorb moisture during storage under relative humidity greater than approximately 85% [46].…”
Section: Compatibility Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it should be noted that lactose monohydrate, one of the excipients in FT formulation, also interacts with moisture-sensitive drugs and affect the stability of the drug [27,44]. Koivisto et al [45] reported that Mg stearate (excipient as well) properties strongly depend on the moisture content and its hydration state [21]. Literature data confirm that magnesium stearate might absorb moisture during storage under relative humidity greater than approximately 85% [46].…”
Section: Compatibility Study Resultsmentioning
confidence: 99%
“…stability of the drug [27,44]. Koivisto et al [45] reported that Mg stearate (excipient as well) properties strongly depend on the moisture content and its hydration state [21]. Literature data confirm that magnesium stearate might absorb moisture during storage under relative humidity greater than approximately 85% [46].…”
Section: Compatibility Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to relying on the swing of cilia on the bronchial wall to push sputum out (Paplińska-Goryca et al , 2020), most of the other sputum expulsion methods involve different fluid dynamic mechanisms. Drugs are generally used to accelerate the secretion of body fluid to reduce the dynamic viscosity of sputum and promote sputum excretion (Pobudkowska et al , 2021). When people can breathe autonomously, they can instantaneously produce large air velocity through severe coughs (Bourouiba et al , 2014; Wei and Li, 2017) and push the sputum upward with the help of inertia.…”
Section: Introductionmentioning
confidence: 99%